ผลของการใช้ที่ดินต่อสมบัติอุทกวิทยาของดินบางประการบริเวณพื้นที่ลุ่มน้ำย่อยห้วยหินดาด จังหวัดระยอง - ถึกสถิตย์ สุภัทรา; วงศ์สิริชัย พุทธรักษ์ (Thai Journal of Science and Technology, 2020)
Different land use types have effects on soil properties, especially soil hydrology. Thus, this research aims were to study and compare some soil hydrological properties in various land uses at Huai Hin Dat subwatershed, Rayong province in 2018. From the results, an average soil porosity was highest in the secondary dry evergreen forest and the lowest in the para rubber area which is opposite to soil bulk density. Soil moisture content was high in the secondary dry evergreen forest at all soil depths and low in forest restoration with teak area. In addition, it was found that soil bulk density and soil moisture content among different land use types and soil depths were highly statistically significant (p < 0.01). For infiltration rates during wet and dry periods, the secondary dry evergreen forest showed the best infiltration capacity with the values between 348-355 mm/hr, while para rubber area was the lowest value with 224-250 mm/hr. And saturated hydraulic conductivity showed the same trend as infiltration capacity. It can be concluded that the types of land use can affect soil hydrological properties differently, which relate to water yield in watershed. Therefore, land use planning and watershed management should be done appropriately.